Pemanfaatan Fitur E-Campus Untuk Inovasi Model Belajar - Nakhma’ussolikhah; Novianti, Cucum; Mizan Sya’roni, Mohamad (ISLAMICA, 2022)
The learning model in the 21st century is a dispute that has not been properly resolved. The form of disputes from learning problems is a measure of the success of the education system in Indonesia. The purpose of this research is to minimize problems, obstacles and chaos in learning in the BBC IAI campus environment. The teaching system on campus prioritizes the development of digital access. The involvement of digital aspects needs to be considered, such as improving facilities that support Android phones, Laptops, WFI, Projectors, Infocus, as well as the compatibility between hardware and software. This research method is a qualitative type of phenomenological design. The results of this study describe that students at the BBC IAI campus have access to an online-based learning system. There are features on the e-campus consisting of several features including discussion columns, task uploads, material uploads, videos, audio, references, attendance, lecturer notes and exams and assessments, lecturers and students can see digital footprints where students and lecturers can access using features e campus for the implementation of online learning applications Jitsi, google meet, Skype, Zoom, Big Blue Button, Whatsapp Group, there is a feature in the notes section for lecturer instructions before learning begins equipped with online absences, the completeness of the e campus feature can make it easier for students, lecturers in the learning process with learning innovations to increase the value of creativity for lecturers and students.